Model Pemilihan Proses untuk Meminimalkan Biaya Manufaktur, Kerugian Kualitas, dan Keterlambatan Pengiriman - Ani Fatmawati; Cucuk Nur Rosyidi; Wakhid Ahmad Jauhari (Jurnal Teknik Industri, 2012)
There are three aspects of competitive strategy that can be applied by manufacturing companies: quality, cost, anddelivery time. Actually, it is hard to produce high quality poducts in low manufacturing cost and on time delivery. Hence, a process selection is needed to integrated the three aspects above in order to meet a customer requirement. This research develops a process selection model to minimize manufacturing cost, quality loss cost, and lateness cost considering component spesification, delivery time, production capacity, and customer order. A numerical example is given to show the application of the model using an assembly product that consists of three components. Three machines are used to produce all of the components. Each machine has different characteristic in manufacturing cost, tolerances, and processing time. Total cost that used to produce 100 unit assembly product is Rp5.390.970,00.